Individualizing endpoints in randomized clinical trials to better inform individual patient care: the TARGET proposal. Issue 1 (December 2016) - Iwashyna, Theodore; Deane, Adam
Abstract In practice, critical care practitioners individualize treatments and goals of care for each patient in light of that patient's acute and chronic pathophysiology, as well as their beliefs and values. Yet critical care researchers routinely measure one endpoint for all patients during randomized clinical trials (RCTs), eschewing any such individualization. More recent methodology work has explored the possibility that enrollment criteria in RCTs can be individualized, as can data analysis plans. Here we propose that the specific endpoints of a RCT can be individualized—that is, different patients within a single RCT might have different secondary endpoints measured. If done rigorously and objectively, based on pre-randomization data, such individualization of endpoints may improve the bedside usefulness of information obtained during a RCT, while perhaps also improving the power and efficiency of any RCT. We discuss the theoretical underpinnings of this proposal in light of related innovations in RCT design such as sliding dichotomies. We discuss what a full elaboration of such individualization would require, and outline a pragmatic initial step towards the use of "individualized secondary endpoints" in a large RCT evaluating optimal enteral nutrition targets in the critically ill.